2019
DOI: 10.3390/ijms20122921
|View full text |Cite
|
Sign up to set email alerts
|

The Pleiotropic Role of Retinoic Acid/Retinoic Acid Receptors Signaling: From Vitamin A Metabolism to Gene Rearrangements in Acute Promyelocytic Leukemia

Abstract: The family of retinoic acid receptors (RARs: RARα, -β, and -γ) has remarkable pleiotropy characteristics, since the retinoic acid/RARs pathway is involved in numerous biological processes not only during embryonic development, but also in the postnatal phase and during adulthood. In this review, we trace the roles of RA/RARs signaling in the immune system (where this pathway has both an immunosuppressive role or is involved in the inflammatory response), in hematopoiesis (enhancing hematopoietic stem cell self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 161 publications
(203 reference statements)
2
15
0
Order By: Relevance
“…PML-RARα alters the functions of both the transcription factor RARα and of the tumor suppressor PML, which is at the hub of the PML nuclear bodies (PML-NBs) [93]. PML-RARα disrupts the PML-NBs and acts as a transcriptional repressor through the block of RA-induced myeloid differentiation, thereby impeding the differentiation from the promyelocyte stage to granulocyte [108]. The PML-RARα fusion protein is not only a misfolded protein by itself, but also promotes aberrant folding of nuclear receptor corepressor 1 (NCOR1), a protein essential for the function of several tumor suppressors, including Max dimerization protein 1 (MAD1) [109].…”
Section: Upr Involvement In Aplmentioning
confidence: 99%
“…PML-RARα alters the functions of both the transcription factor RARα and of the tumor suppressor PML, which is at the hub of the PML nuclear bodies (PML-NBs) [93]. PML-RARα disrupts the PML-NBs and acts as a transcriptional repressor through the block of RA-induced myeloid differentiation, thereby impeding the differentiation from the promyelocyte stage to granulocyte [108]. The PML-RARα fusion protein is not only a misfolded protein by itself, but also promotes aberrant folding of nuclear receptor corepressor 1 (NCOR1), a protein essential for the function of several tumor suppressors, including Max dimerization protein 1 (MAD1) [109].…”
Section: Upr Involvement In Aplmentioning
confidence: 99%
“…It is a natural inhibitor of human tumors and is commonly used in the treatment of many diseases (Fischer‐Huchzermeyer et al., 2017; Rizzoli & Biver, 2018). However, a large body of research has shown that long‐term use of retinoic acid can cause a variety of diseases, with OP being the most important one (Conserva, Anelli, Zagaria, Specchia, & Albano, 2019; Petkovich, Heersche, Aubin, Grigoriadis, & Jones, 1987). We therefore chose to treat rats with retinoic acid to create a secondary OP model.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein (P-gp) and multidrug resistance-associated protein 1 (MRP1) are induced by arsenic trioxide (As2O3), but are not the main mechanism of As2O3 -resistance in acute promyelocytic leukemia cells [78] Very little is known on the role of the microenvironment in APL. Several studies have shown that RARs regulates non-hematopoietic cells present in the bone marrow microenvironment influencing stem cell fate [79][80][81].…”
Section: Insight Into the Mechanisms Of Treatment Resistance In Aplmentioning
confidence: 99%